ANALISIS KOMPARATIF KLASTERISASI PENERIMA BANTUAN SOSIAL MENGGUNAKAN METODE TOPSIS DAN SAW - Librado, Dison; Prabawa, Tri (Lembaga Penelitian dan Pengabdian Masyarakat - Universitas Teknologi Digital Indonesia, 2024)
Decision support system becomes the subject of this research with the object on the Direct Cash Assistance Program for the community sourced from the Village Funds to reduce the burden on the poor and vulnerable to poverty from the impact of the COVID-19 pandemic. From the two methods, namely the TOPSIS method and the SAW method, a comparison will be made on the results obtained to see how appropriate the distribution of social assistance is carried out. The program implemented in Wedomartani Village covers a fairly large area with a large population. The problem is the large number of prospective beneficiaries that isn't proportional to the available social assistance quota, so it is necessary to select the recipients based on predetermined criteria in order to be on target. A decision support system is deemed necessary to support policy makers in determining the choice of recipients to be on target. From the results of processing with the TOPSIS method and the previous SAW method, if the top 25 rankings are taken, they both show that the distribution of the population's poverty level is uneven, so there needs to be a village government policy for more specific poverty alleviation.